(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines how secondary teachers’ comprehension questions are related to students’ critical thinking. Using a descriptive-analytical design, we observed lessons, analysed teachers’ preparation books, and administered questionnaires and semi-structured interviews. A corpus of 137 classroom questions was coded according to Bloom’s cognitive levels. Lower-order questions (remembering, understanding) accounted for 66% of all prompts, whereas higher-order questions (analysis, evaluation, creation) represented 20%. The interviews indicated that time constraints, curriculum coverage pressures, and limited training in question design were key barriers to higher-order questioning. Although the students reported greater motivation when they were asked open-ended questions, fewer than half felt free to respond to them. The findings suggest an association between question quality and opportunities for critical thinking, highlighting the need for targeted teacher professional development and assessment practices that value analytical responses. The implications and limitations related to sampling, coding reliability, and generalizability are discussed.